Auditive training effects from a dichotic listening app in children with dyslexia. (12th November 2018) - Helland, Turid; Morken, Frøydis; Bless, Josef J.; Valderhaug, Hanna V.; Eiken, Monica; Helland, Wenche A.; Torkildsen, Janne v.K.
Abstract : Dichotic listening (DL) taps information on the brain's language laterality, processing, and attention. Research has shown that DL responses in dyslexia deviate from the typical pattern. Here, effects of DL training and its correspondence to rapid naming (RAN) and digit span (DS) in typical children and children with dyslexia were assessed. Three groups of third graders participated: two training groups, control training (CT) and dyslexia training (DT), and a control group that received no training (control no training, CnT). All took part in testing pretraining and posttraining. DL measures were on laterality, response scores, and attention. The three groups showed different response patterns: minor changes in CnT, change in all measures in CT, and some changes in DT. RAN and DS scores correlated significantly with some of the DL measures, especially with the attention scores. Our findings support arguments that brain architecture for language in dyslexia is lateralised in the same way as in children without dyslexia. However, the ability to modulate attention during DL is weaker in dyslexia than in typically developing children. A training‐induced normalisation of lateralisation was observed in free recall in the dyslexia group, which suggests that DL training may be a promising intervention approach.